Association of apolipoprotein E genotypes, blood pressure, blood lipids and ECG abnormalities in a general population aged 85+ - Rastas, Sari (BMC Geriatr, 2004)
BACKGROUND: Several studies have linked apolipoprotein E (ApoE) ε4 allele with elevated cholesterol and blood pressure levels. Data on the association of APOE genotypes with blood pressure, lipids, atrial fibrillation and ECG abnormalities in individuals aged 85 years and over is sparse. METHODS: This cross sectional study consisted of all residents of the city of Vantaa (N = 601) aged 85 years or over of whom 505 participated in the study. Blood pressure was measured by using mercury sphygmomanometer. 12-Lead ECG, short ambulatory ECG, or both were taken from all study subjects to diagnose atrial fibrillation (AF). Ambulatory ECG was carried out home or in the institute. APOE genotyping was performed using a combination of the polymerase chain reaction (PCR) and solid-phase minisequencing technique. Statistical analysis was made by using Kruskall-Wallis-test (continuous data) and χ(2)-test (rates and proportions). RESULTS: In these very elderly individuals, APOE 4 allele was significantly associated with elevated cholesterol and low-density lipoprotein (LDL) levels. Blood pressure or cardiac arrhythmias did not differ between APOE genotypes. CONCLUSIONS: These observations suggest that the important role of APOE genotype still influences cardiovascular risk profile even among the very elderly people.